Triterpenes from Celastrus hindsii Benth. - Thuy, Trinh Thi; Cuong, Nguyen Huy; Sung, Tran Van (Vietnam Journal of Chemistry, 2014)
Chemical investigation of the leaves of Celastrus hindsii growing in Quang Binh, Vietnam led to the isolation and structural elucidation of three triterpenes, 3-friedelanol, 3-friedelanone and canophyllol. These structures were determined on the basis of MS and NMR spectroscopic data. Keywords: Celastrus hindsii, celastraceae, friedelanol, friedelanone, canophyllol.